Understanding Mapuche-Williche Conceptions of Diabetes Mellitus and Arterial Hypertension from the Perspective of Intercultural Health - Sergio Hernán Bermedo Muñoz (Social Medicine Publication Group, 2016)
Background: In order to create a culturally relevant health model, we examined how users from the Mapuche-Williche community, Chile's largest indigenous population, understood the causes of Diabetes Mellitus and Hypertension. Objective: To describe both popular conceptions and traditional therapeutic practices used by Mapuche-Williche patients with Diabetes and Hypertension. Setting: Health clinics located in the Cacicado de Riachuelo Jurisdiction of Rio Negro. Materials and Methods: This is an exploratory/descriptive study using the techniques of Social Anthropology to incorporate elements of indigenous health concepts into the positivist logic of biomedicine. Recruitment was non-random. We employed both case studies and in-depth interviews. Interviews were analyzed by constructing categories which described the meanings and significance that the interviewees themselves saw in their understandings and practice. Results: As explained by our patients, the Mapuche-Williche cultural system involves a therapeutic process during which traditional Mapuche-Williche medicine may complement, alternate with, or substitute for traditional Allopathic Medicine. Conclusions: Diabetes Mellitus and Hypertension are not recognized illnesses within traditional Mapuche-Williche medicine. This creates difficulties in terms of adherence to biomedical treatment. Patients substitute traditional healing for biomedicine. These considerations suggest the need to develop an intercultural health model within the commune of Rio Negro.